Manajemen Konflik dalam Rumah Tangga Perspektif Firanda Andirja - Zahratunnisa Zahratunnisa; Irsan Irsan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to examine the types of conflicts that occur in households and conflict management from Firanda Andirja's perspective. This research uses descriptive qualitative method. Data was collected from uploading video recordings of Firanda Andirja's lectures on his youtube page, related books, government publication data related to divorce cases, and a collection of related scientific journals. The results show that there are 5 types of conflict in households, namely Conflict-habituated marriages, Devitalized relationships, Passive-congenial, Vital and Total marriages. The results of this study also show that there are 5 methods of conflict management according to Firanda Andirja, namely 1) Silent and Smile method, 2) The method of ignoring the conflict that occurs, 3) The method of joking and laughing, 4) The method of discussion and communication with politeness, 5) Resolving problems with good manners and morals.